2014
DOI: 10.1186/preaccept-1786708675141265
|View full text |Cite
|
Sign up to set email alerts
|

Construction and in vitro evaluation of a recombinant live attenuated PRRSV expressing GM-CSF

Abstract: Background: Porcine reproductive and respiratory syndrome virus (PRRSV) continues to be an important problem for the swine industry. Inactivated vaccines and modified-live virus vaccines are widely used in the field; however, the efficacy of these PRRSV vaccines is suboptimal due to poor immunogenicity. Granulocyte-macrophage colony stimulating factor (GM-CSF) has been extensively used as an effective genetic and protein adjuvant to enhance the efficiencies vaccines expressing tumor or pathogen antigens. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In another attempt, granulocyte–macrophage colony-stimulating factor (GM-CSF) was inserted in a PRRSV vaccine strain. The inserted gene was stably expressed upon serial passaging in vitro , and the presence of GM-CSF led to increased surface expression of MHCI+, MHCII+, and CD80/86+ (Yu et al. 2014).…”
Section: Overview Of Empirical Resultsmentioning
confidence: 99%
“…In another attempt, granulocyte–macrophage colony-stimulating factor (GM-CSF) was inserted in a PRRSV vaccine strain. The inserted gene was stably expressed upon serial passaging in vitro , and the presence of GM-CSF led to increased surface expression of MHCI+, MHCII+, and CD80/86+ (Yu et al. 2014).…”
Section: Overview Of Empirical Resultsmentioning
confidence: 99%
“…GM-CSF is a multi-functional immune modulator, playing an important role in the differentiation of the progenitor cells into DCs in vitro and in vivo [ 44 ] and it has been employed as an adjuvant to enhance the immunogenicity in many viral vaccines [ 39 , 45 - 52 ]. In our studies, it was found that expression of GM-CSF by RABV could result in the recruitment and activation of more DCs than the parent virus in the murine [ 38 , 39 ] as well as in the canine model via parenteral as well as oral routes.…”
Section: Discussionmentioning
confidence: 99%
“…As a potential remedy to this problem, foreign gene was inserted between PRRSV ORF1b and ORF2a, along with a copy of TRS. This approach had particular advantage of minimizing the effects of expression and post-translational modification of viral proteins [ 33 ], and a series of recombinant PRRS viruses have been constructed using this approach [ 33 37 ]. In this study, the pIL-4 gene was inserted between N gene and 3′-UTR of a live attenuated PRRSV infectious clone using a similar strategy.…”
Section: Discussionmentioning
confidence: 99%